Photoconductivity relaxation and electron transport in macroporous silicon structures - Karachevtseva, L.A.; Onyshchenko, V.F.; Sachenko, A.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2017)
Kinetics and temperature dependence of photoconductivity were measured in macroporous silicon at 80…300 K after light illumination with a wavelength of 0.9 μm. The influence of mechanisms of the charge carrier transport through the macropore surface barrier on the kinetics of photoconductivity at various temperatures was investigated. The kinetics of photoconductivity distribution in macroporous silicon and Si substrate have been calculated using the finite-difference time-domain method. The maximum of photoconductivity has been found both in the layer of macroporous silicon and in the monocrystalline substrate. The kinetics of photoconductivity distribution in macroporous silicon showed rapid relaxation of the photoconductivity maximum in the layer of macroporous silicon and slow relaxation of it in the monocrystalline substrate.